HUBUNGAN ANTARA MATA KULIAH FISIKA TERAPAN DALAM KONTRIBUSINYA TERHADAP MATA KULIAH KEAHLIAN PADA MAHASISWA PROGRAM DIPLOMA III TEKNIK ELEKTRO SEKOLAH VOKASI UNIVERSITAS DIPONEGORO - Setiono, Iman; Tadeus, Dista Yoel (Gema Teknologi, 2018)
Iman Setiono, Dista Yoel Tadeus, in this paper explain that physics is a branch of behavior and experimental studies. In studying the nature, physics uses mathematical language to model natural phenomena in a mathematical context. In physics research, mathematical abilities are needed as student’s initial abilities in solving Physics problems. This study aims to study the relationship between courses in applied physics and courses that are the basis of developing competencies. The method used is the method of documentation and analysis using quantitative descriptive. The object of this study was students for physics subjects from student learning outcomes of student KHS grades. The results obtained from an integrated analysis provide strong results between learning outcomes and the ability of other subjects.